Perancangan Sistem Informasi Penetapan Bonus Karyawan Berbasis Web Menggunakan Metode Personal Extreme Programming: Studi Kasus Babycos.Id - Aulia Lintang Sinawang (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Babycos.id a home-based business in the distribution of baby and children's supplies, was founded in 2018 in South Tangerang with a focus on sales through online platforms such as Shopee, Lazada, and Tiktok Shop. In facing increasingly fierce business competition, employee management becomes a crucial aspect, especially in the transparent and objective determination of bonuses. The determination of bonuses is considered a form of reward that can boost employee motivation. This outlines the rapid development of Babycos.id's e-commerce in 2022. To motivate employees, the owner of Babycos.id aims to provide significant rewards. Despite the increase in revenue, the management of employee bonus data is still conducted manually through WhatsApp groups, resulting in errors and lengthy calculation times. To address these issues, the author has designed a web-based employee bonus information system, applying the Personal Extreme Programming method. The use of a website-based method with PHP programming language and MySQL database is expected to provide an effective and efficient solution for employee bonus management at Babycos.id. The anticipated outcome is a system capable of addressing existing issues and making a positive contribution to enhancing employee motivation and performance.